HYBRID INTELLIGENCE (HI) IN THE HOSPITALITY INDUSTRY: EFFECTS ON TRUST, PERCEIVED SERVICE QUALITY AND CUSTOMER SATISFACTION: Received: 16th February 2026, Revised: 20th February 2026, 23rd February 2026, Accepted: 09th March 2026, Date of Publication: 18th March 2026 - Hasna El Hamzaoui,; Imane Ghazlane, (PEOPLE: International Journal of Social Sciences, 2026)
In an emerging country like Morocco, the hospitality sector is facing gradual transformations due to the integration of artificial intelligence technologies, such as check in kiosks, chatbots, and assistance robots. While this dynamic is still limited and heterogeneous, it aims to improve service efficiency and personalize the customer experience, while also raising questions about the acceptability of these systems and their effects on three main dimensions of customer experience: perceived service quality, trust, and customer satisfaction. Given the limitations of fully automated services, hybrid intelligence, defined as collaboration between AI and human intelligence, appears as an alternative option that combines the relational component with technological efficiency. This study aims to examine the comparative impact of three types of hotel reception modalities; Human-only reception, AI-only reception, and reception based on hybrid intelligence on the three main dimensions of customer experience. To this end, we adopted a quantitative approach based on a comparative questionnaire administered to Moroccan hotel guests who have stayed at least once in a 4- or 5-star hotel in Marrakech. The results confirm that the hybrid model, where clients interact with AI and humans, generate higher levels of trust, perceived quality and satisfaction than either a purely human or purely AI based reception. The results also indicate that customers familiar with AI use demonstrate a higher degree of trust in AI-based systems. Furthermore, customers with a strong relationship orientation report being satisfied with the experience offered by hybrid or human-dominated models. This study enriches the understanding of the role of hybrid intelligence in hotel services within the Moroccan context and offers practical recommendations for hotels wishing to integrate AI technologies without compromising the customer experience. Due to the use of scenarios and a convenience sample, this study has limitations in terms of generalizing the results. However, it opens up avenues for future research based on real-world experimentation and the integration of in-depth qualitative approaches.